Quality management in Kazakhstan. (Journal of Economic Research & Business Administration, 2016)
In developed countries, the problem of improving the quality takes a leading place in ensuring competitiveness of products and services, building a new relationship between the consumer and the manufacturer, satisfaction of material needs, social interests and spiritual needs. With the release of the Kazakh enterprises on international markets and the opening of the Kazakh market for the products of foreign companies, the issue of product quality has become a priority for the domestic producers. Achieving the required quality or special defense technology requires the development of additional measures, especially at the stage of research and development activities, and the establishment of appropriate structures responsible for quality control. Questions certification of products at the same time also have their own specifics. The article deals with the control of the quality in Kazakhstan. The focus is on modern systems of quality management products and services to meet the requirements of ISO 9000 are also presented on the composition of materials and the quality system certification of enterprises, guidance on the application of statistical methods of quality management in Kazakhstan.
Keywords: quality; management; international standards; management systems certification.